The Effect of Parenting Styles on the Behavior of Children in Nabweru Sub-county - Dorcas Namwase Bikufa (Uganda Christian University, 2024)
The study examined the effect of parenting styles on the behavior of children in Nabweru Sub-County, Uganda. The research found that there are four main parenting styles present in the community: authoritative, authoritarian, permissive, and neglectful. The results showed that authoritative parenting, characterized by warmth and appropriate control, was associated with children who were more independent, self-reliant, and well-behaved. In contrast, authoritarian parenting, which emphasizes strict obedience, was linked to children experiencing anxiety and insecurity. Permissive parenting, where parents are uninvolved, led to more independent but sometimes misbehaved children. Neglectful parenting, where parents are emotionally and physically unavailable, had the most negative impact on children's social skills, academic success, emotional well-being, and behavior. The study also explored the factors influencing the adoption of different parenting styles in Nabweru, including cultural beliefs and a desire to break from negative traditional practices. Overall, the findings highlight the significant influence of parenting styles on shaping children's behavior and development within this specific cultural context.